The Effect Of Giving Warm Water Immersion Therapy For Oedema Of The Legs Of Pregnant Women Third Trimester At Pratama Clinic Cahaya Lubuk Pakam - Arisman, Yessy; Elvi Era Liesmayani; Zulianti, Puteri; Desika Wali Pardede (JURNAL KEBIDANAN KESTRA (JKK), 2024)
During pregnancy there are changes in pregnant women, both physical and psychological, which often make pregnant women feel uncomfortable, Swelling in the legs is one of the pregnancy discomforts that pregnant women often complain about and 80% are found in pregnant women in the third trimester. Oedema causes discomfort in pregnant women and can even hinder some activities (1). This study aims to determine the effect of warm water soaking therapy on leg oedema in pregnant women in the third trimester. This study uses a quantitative research design with a one-group pretest-posttest design model, namely observations are made on samples before being given warm water therapy and observations are made again after being given warm water therapy. Samples were taken by purposive sampling. Based on the probability of the test results listed in the table, it can be known that the resulting probability is 0.01. This means that the probability < level of significance (? = 0.05), so that Ha is accepted and H0 is rejected. This means that there is a significant difference between lower limb oedema in pregnant women in the third trimester before giving warm water soaking (Pretest) and oedema of the lower limbs in pregnant women in the third trimester after giving warm water soaking (Postest). Therefore, it can be concluded that there is an Effect of Warm Water Soaking on the Increase of Leg Oedema in Pregnant Women in the Third Trimester at the Pratama Cahaya Lubuk Pakam Clinic in 2024.